Investigation of the Anticancer Potential of Vernonia amygdalina Methanol Extract: A New Hope for MDA-MB-231 Breast Cancer Therapy - Ivan Junius Mesak; Ardhi Broto Sumanto (Biology, Medicine, & Natural Product Chemistry, 2026)
MDA-MB-231 is a breast cancer cell line derived from metastatic adenocarcinoma and classified as a triple-negative breast cancer (TNBC) subtype. This breast cancer subtype is highly aggressive, has a high recurrence rate, and offers limited treatment options due to the absence of estrogen, progesterone, and HER-2 receptor expression. Therefore, the development of advanced therapeutic strategies is urgently needed to inhibit the metastasis of TNBC cancer cells. This study aimed to investigate the potential of the methanol extract of Vernonia amygdalina leaves as a natural chemotherapeutic agent for metastatic breast cancer therapy, with a focus on inducing cell death through apoptosis mechanisms. This study was an experimental research that began with the collection and identification of raw materials, followed by the preparation of simplicia, extraction processes, and phytochemical screening. Subsequently, cytotoxicity testing was conducted using the MTT assay, cell cycle analysis was performed using the PI-staining assay, and apoptosis was assessed using the Annexin V/PI-staining assay, all of which were analyzed through flow cytometry. The methanol extract of V. amygdalina demonstrated a moderate cytotoxic effect with an IC50 value of 109.36 µg/mL. The extract induced S-phase cell cycle arrest in a dose-dependent manner, indicating its ability to reduce cell viability by inhibiting DNA replication. In the apoptosis assay, the highest percentage of cell death (3.12%) was observed at the concentration of 54.5 µg/mL, suggesting that this dose produced the strongest apoptotic response among the treatments tested. The methanol extract of V. amygdalina leaves shows potential as a natural chemotherapeutic agent for metastatic breast cancer. The extract can induce cancer cell death through apoptosis, indicating its promise for further development as a supportive anticancer therapy.